Concerning the timing of antibiotic administration in women undergoing caesarean section: a systematic review and meta-analysis. Issue 4 (18th April 2013) - Heesen, Michael; Klöhr, Sven; Rossaint, Rolf; Allegeaert, Karel; Deprest, Jan; Van de Velde, Marc; Straube, Sebastian
Abstract : Objective: To assess the effects on maternal infectious morbidity and neonatal outcomes of the timing of antibiotic prophylaxis in women undergoing caesarean section. A recent National Institute for Health and Clinical Excellence (NICE) guideline reported that antibiotic administration before skin incision reduces the risk of maternal infection; this recommendation was based on a meta-analysis, however one including trials that were not double blind and not including a trial published recently. Design: Systematic review and meta-analysis. Data sources: Searches of PubMed and EMBASE and reference lists of the retrieved articles. Inclusion criteria: Randomised double-blind controlled trials comparing the administration of antibiotics before skin incision with administration after cord clamping. Data extraction and analysis: Data on maternal total infectious morbidity, endometritis and wound infection, as well as neonatal intensive care unit admission, neonatal infection and neonatal sepsis were extracted and combined using random effects meta-analysis. Results: Five studies reporting on 1777 parturients were included in our systematic review. The relative risk (RR) for maternal total infectious morbidity for antibiotic administration before incision compared with antibiotic administration after cord clamping was 0.64 (95% CI 0.36 to 1.15). Likewise, there was no difference in the risk of wound infection (RR 0.72, 95% CI 0.41 to 1.27). Parturients receiving the antibiotic preoperatively had a significantly reduced risk of endometritis (RR 0.48, 95% CI 0.27 to 0.87; number needed to treat 41, 95% CI 23 to 165). Analyses of the neonatal outcome parameters revealed no differences between the regimens of antibiotic administration, but were based on few studies. Conclusions: In contrast to a recent NICE guideline, we did not find a reduction in total infectious morbidity with antibiotic administration before skin incision; we confirmed a reduction in the risk of endometritis and a lack of effect on the risk for wound infection.